Laboratory-Based Assessment of Seed Germination in Raphanus Sativus Var. Japanese White Following Exposure to Heavy Metals Lead (Pb) and Cadmium (Cd) - Indwar, Tanesh (Journal of Research in Science and Engineering, 2025)
One of the most important constituents of multifactorial environment which exert its operative influence on any and every ontogenic phase in life cycle of a plant, is water. The water gets polluted as the washouts from catchment area brings along with it various metallic ions, e. g. nickel, zinc, cadmium, lead, arsenic, copper, etc. Many of these are highly toxic and often accumulated by plants. The accumulation of toxic metals in crops is receiving a great deal of attention. There are a few reports on the hazardous impact of toxic elements lead and cadmium on the germination of seeds of Raphanus sativus. Raphanus sativus L. a common vegetable crop of India was chosen as an experimental material for the present investigation. Radishes are grown as winter, spring, late summer and autum varieties in different countries mostly in India China and Japan. It is perhaps one of the most quickly and easily grown vegetable of kitchen garden. The variety of radish considered in the present investigation is Japanese white which is an asiatic or tropical type variety of radish. In the present study the seeds of experimental plant Raphanus sativus cultivar Japanese white were examined after treated with various concentrations of heavy metals, Cd (cadmium) and Pb (lead) respectively using their salts i. e. cadmium chloride and lead nitrate under laboratory conditions. Gradual decline was observed in seed germination of Raphanus sativus cultivar Japanese white with increase in heavy metal concentrations. It was observed that in control condition the seeds showed maximum (95 - 100%) germination. Whereas treated seeds showed 40% (Cd) and 50% (Pb) germination. Statistically very highly significant differences were observed between the control and various treatments and also among various treatments (concentrations). No such differences were observed among the chemicals.